An inexpensive direct reading tensiometer - Camargo, Ângelo Paes de; Grohmann, Francisco; Camargo, Marcelo B. Paes de (Pesquisa Agropecuaria Brasileira, 2014)
A transparent tube tensiometer was developed and tested to establish the relationship between the visible chamber height and the tension read in the manometers. The regressions follow the law of perfect gas (Boyle & Mariotte) and may be expressed by hiperbolic equations. The constants of the equations varies with the initial chamber height. The best values of initial chamber height were between 0.5 to 1.0 cm, corresponding to the equation: y = 800x/ (x + 1.8), where y is the tension (mb) and x the chamber height (cm). The direct reading tensiometer described here makes unnecessary the manometers so making the tensiometer inexpresive and more reliable.
Keywords: soil water; Boyle & Mariotte law